The Neotropical tanyderid Araucoderus gloriosus (Alexander) (Diptera, Tanyderidae), with description of the egg, larva and pupa, redescription of adults, and notes on natural history - Madriz, R. Isaí; Courtney, Gregory W. (Zootaxa, 2016)
Larvae, pupae and adults of Araucoderus gloriosus (Alexander) were collected during fieldwork in Chilean Patagonia, December 2013 and January 2014. Eggs were obtained from females that oviposited in captivity. Association of all life stages is based on co-occurrence and rearing of individual larvae to adults. A diagnosis for the genus and species is provided. Descriptions of the egg, larva and pupa and redescriptions of the male and female are completed. Eggs of A. gloriosus are the first described for Tanyderidae. Natural history characteristics for this species, including microhabitat, copulatory behavior and oviposition, are discussed.